Cockayne syndrome misdiagnosed as cerebral palsy : a case report. - Vafaee, Amir Reza; Baghdadi, Taghi; Norouzzadeh, Sara (Iranian Journal of Child Neurology, 2018)
Abstract A 7 years old patient was referred to our pediatric orthopedic clinic with the diagnosis of cerebral palsy. His parents were concerned about some inconsistencies in his disease progression. After initial evaluations, we were convinced that the diagnosis of cerebral palsy was incorrect. The true diagnosis was suspected and confirmed with molecular genetic analysis. A rare autosomal recessive disorder –cockayne syndrome- has been diagnosed. Although untreatable, it can be prevented by appropriate prenatal diagnostic tests for their future children.